Carbon Transformation in Biofouling During Membrane Filtration: A Review of Challenges and Solutions in Palestine. - Al Bahri, Juhaina (Palestine Polytechnic University, 2025)
Biofouling is a significant impediment to efficient membrane filtration in Palestine, notably in the Gaza Strip, where nearly all groundwater is contaminated and access to clean water is severely restricted. In my review, I look at how dissolved organic carbon (DOC) from local sources such olive oil wastewater, agricultural runoff, and leaking septic systems promotes microbial growth and extracellular polymeric substance (EPS) formation, resulting in rapid membrane fouling. Using recent studies and regional data, I investigate biofouling mechanisms in Gaza's unique environmental and infrastructure conditions. I assess mitigation techniques, including low-cost biological pretreatment using olive waste biochar, O₃-PAC oxidation, and new approaches such as quorum quenching and machine learning-based monitoring. Policy initiatives, such as strengthening sanitation infrastructure and promoting cross-border collaboration with Jordan, are also addressed. While modern technologies offer promise, their deployment in Gaza is limited due to a lack of analytical tools, financing, and technical capacity. This assessment emphasizes the need for integrated, context-sensitive solutions that combine local resource use, scalable technologies, and institutional assistance to improve water security in Palestine. This analysis synthesizes findings from peer reviewed research published from 2000 to 2024, obtained from sources such as Scopus and Web of Science, with an emphasis on biofouling mechanisms and mitigation measures relevant to water-scarce and conflict-affected locations like Palestine.
Number of pages: 3, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Carbon Transformation, Biofouling, Membrane Filtration